Financial Soundness Indicators and the Characteristics of Financial Cycles - Che, Natasha (IMF Working Papers; Working Paper, 2014)
Better 'financial soundness' of banks could help mitigate the volatility of financial cycles by reducing banks' risk exposure. But trying to improve financial soundness in the midst of a downturn can do the opposite-further aggravating the contraction of credit. Consistent with this notion, the paper found that better initial scores in certain financial soundness indicators (FSIs) are associated with milder and shorter downturns; and improving FSIs during a downturn worsens the shrinkage of credit and amplifies the cycle. In this context, our results suggest that policy makers should be mindful about the timing of regulating changes in banks' FSIs.